2020
DOI: 10.1534/g3.119.400957
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Diversity in theCamelinaGenus Provides Insights into the Genome Structure ofCamelina sativa

Abstract: Camelina sativa (L.) Crantz an oilseed crop of the Brassicaceae family is gaining attention due to its potential as a source of high value oil for food, feed or fuel. The hexaploid domesticated C. sativa has limited genetic diversity, encouraging the exploration of related species for novel allelic variation for traits of interest. The current study utilized genotyping by sequencing to characterize 193 Camelina accessions belonging to seven different species collected primarily from the Ukrainian-Russian regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
94
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(115 citation statements)
references
References 53 publications
13
94
1
7
Order By: Relevance
“…Defining the relationships between the camelina species may help to identify species that are potential novel sources of allelic variation for introgression into C. sativa [51]. So far, little genetic diversity exists in currently available C. sativa cultivars limiting the effectiveness of traditional breeding programs [52][53][54].…”
Section: Genomic Content Of C Sativamentioning
confidence: 99%
“…Defining the relationships between the camelina species may help to identify species that are potential novel sources of allelic variation for introgression into C. sativa [51]. So far, little genetic diversity exists in currently available C. sativa cultivars limiting the effectiveness of traditional breeding programs [52][53][54].…”
Section: Genomic Content Of C Sativamentioning
confidence: 99%
“…Previous research has reported a unique seed FA composition and exceptionally high erucic acid content in C. neglecta when grown in controlled environments [36]. Additional sampling and characterization of C. neglecta populations may provide a promising avenue for crop improvement, as recent studies have uncovered up to two of the three subgenomes of C. sativa to be derived from C. neglecta or a close relative [16,37]. Resynthesis of this hexaploid crop may prove possible as is the case in Brassica and the 'Triangle of U' [38], thus facilitating additional natural diversity and agronomic traits for crop improvement [15].…”
Section: Geographical and Climatic Distributions Of Camelina Speciesmentioning
confidence: 99%
“…Wild camelina may represent a valuable source of genetic diversity for this species in future breeding programs in Europe. The allohexaploid genome of camelina is sequenced and embraces approximately 788.6 MB, containing approximately three times more genes than Arabidopsis thaliana and with the highest genetic density among sequenced plant genomes (Chaudhary et al 2020;Kagale et al 2016). Even though it has a sequenced genome, information on camelina genes controlling important traits is still lacking.…”
Section: Genetic Diversity and Breeding Strategiesmentioning
confidence: 99%